Ellagitannins in Finnish plant species – Characterization, distribution and oxidative activity - Moilanen, Johanna (fi=Turun yliopisto|en=University of Turku|, 2015)
Ellagitannins are secondary metabolites that are produced by plants. Among other features, they are assumed to function as plants’ defensive compounds against plant-eating herbivores. This thesis focuses on a theory, which suggests that the biological activity of ellagitannins is based on their tendency to oxidize at the highly alkaline gut conditions of insect herbivores (oxidative activity). To study the biological activities of ellagitannins, a wide variety of structurally different ellagitannins were purified from different plant species by using liquid chromatographic techniques. The structures were characterized with the aid of spectrometric methods. Based on the acquired data, it was also possible to create a scheme, which enables the classification and even identification of ellagitannins from plant extracts without the need to isolate each compound for individual characterization. The biological activities of ellagitannins were determined with methods that are based on the abilities of the compounds to scavenge radicals, chelate iron ions, and on their rate of oxidation at high pH. The results showed that ellagitannins possess oxidative activities both at high and neutral pH, and that their activities depend on structure. The occurrence, distribution and content of ellagitannins in Finnish plant species were also studied. The specific ellagitannin profiles of the studied plant species were found to correlate well with their taxonomic classification.

Ellagitanniinit suomalaisissa kasveissa – Karakterisointi, esiintyminen ja oksidatiivinen aktiivisuus Ellagitanniinit ovat kasvien tuottamia sekundääriyhdisteitä, joiden oletetaan toimivan muun muassa kasvien puolustusyhdisteinä niitä ravintonaan käyttäviä kasvinsyöjiä vastaan. Tämän väitöskirjan pääpaino on teoriassa, jonka mukaan ellagitanniinien biologinen aktiivisuus perustuu niiden hapettumisherkkyyteen (oksidatiiviseen aktiivisuuteen) hyönteistoukkien ruoansulatuskanavan korkeassa pH:ssa. Biologisen aktiivisuuden määrittämiseksi rakenteeltaan erilaisia ellagitanniineja puhdistettiin eri kasvilajeista nestekromatografisin menetelmin. Rakenteet karakterisoitiin spektrometrisin menetelmin. Saadun aineiston pohjalta luotiin myös kaavio, jonka avulla ellagitanniinien luokittelu ja jopa tunnistaminen on mahdollista tehdä suoraan kasviuutteesta, ilman että yksittäisiä yhdisteitä tarvitsee eristää ja puhdistaa tunnistamista varten. Biologisen aktiivisuuden määrittämiseksi käytettiin menetelmiä, jotka perustuvat yhdisteiden radikaalinsieppauskykyyn, kykyyn kelatoida metalli-ioneja sekä hapettumisnopeuteen korkeassa pH:ssa. Tulokset osoittivat, että ellagitanniinit ovat oksidatiivisesti aktiivisia sekä korkeassa että neutraalissa pH:ssa, ja että niiden aktiivisuus riippuu rakenteesta. Lisäksi työssä tutkittiin ellagitanniinien esiintymistä suomalaisissa kasveissa sekä sitä, kuinka paljon ja minkä tyyppisiä ellagitanniineja eri kasvilajit tuottavat. Kasvien ellagitanniinikoostumusten havaittiin korreloivan hyvin niiden taksonomisen luokittelun kanssa.